Brazilian Ironstone Plant Communities as Reservoirs of Culturable Bacteria With Diverse Biotechnological Potential - Caneschi, Washington L.; Felestrino, Érica B.; Fonseca, Natasha P.; Villa, Morghana M.; Lemes, Camila G. de C.; Cordeiro, Isabella F.; Assis, Renata de A. B.; Sanchez, Angélica B.; Vieira, Izadora T.; Kamino, Luciana H. Y.; do Carmo, Flávio F.; Garcia, Camila C. M.; et al. (Frontiers in Microbiology, 2018)
Extensive mineral extractivism in the Brazilian Iron Quadrangle region has destroyed large areas of land, decimating plant species and their associated microbiota. Very little is known about the microbiota of the region; hence, cultivable bacteria associated with plants of its soils were investigated for their biotechnological potential. Samples were collected from nine plant species and six soils, and 65 cultivable bacterial isolates were obtained. These represent predominantly gram-positive bacilli (70%) capable of producing amylases (55%), proteases (63%), cellulases (47%), indole acetic acid - IAA (46%), siderophores (26%) and to solubilize phosphate (9%). In addition, 65% of these were resistant to ampicillin, 100% were sensitive to tetracycline, and 97% were tolerant to high arsenic concentrations. Three isolates were studied further: the isolate FOB3 (Rosenbergiella sp.) produced high concentrations of IAA in vitro in the absence of tryptophan – shown by the significant improvement in plant germination and growth rate where the isolate was present. For isolates C25 (Acinetobacter sp.) and FG3 (Serratia sp.), plasmids were purified and inserted into E. coli cells where they modified the physiological profile of the transformed strains. The E. coli::pFG3B strain showed the highest capacity for biofilm production, as well as an increase in the replication rate, arsenic tolerance and catalase activity. Moreover, this strain increased DNA integrity in the presence of arsenic, compared to the wild-type strain. These results help to explain the importance of bacteria in maintaining plant survival in ferruginous, rocky soils, acting as plant growth promoters, and to highlight the biotechnological potential of these bacteria.